Compulsory schooling reforms, education and mortality in twentieth century Europe - Gathmann, Christina; Jürges, Hendrik; Reinhold, Steffen (Social science & medicine, 2015)
Education yields substantial non-monetary benefits, but the size of these gains is still debated. Previous studies report causal effects of education and compulsory schooling on mortality ranging anywhere from zero to large and negative. Using data from 18 compulsory schooling reforms implemented in Europe during the twentieth century, we quantify the average mortality gain and explore its dispersion across gender, time and countries. We find that more education yields small mortality reductions in the short- and long-run for men. In contrast, women seem to experience no mortality reductions from compulsory schooling reforms.